OntoReST: A RST-based Ontology for Enhancing Documents Content Quality in Collaborative Writing - Naja-Jazzar, Hala; de Silva, Nishadi; Skaf-Molli, Hala; Rahhal, Charbel; Molli, Pascal (INFOCOMP Journal of Computer Science, 2009)
Collaborative writing is the process by which more than one author contributes to the content of a document. Although, multi-synchronous collaboration is very efficient in reducing task completion time, it is well known for producing documents of poor-quality content. Most existing collaborative writing environments do not really check the logical arrangement of documents portions (i.e. sentences, paragraphs,...). They rely on authors to verify the content quality of the document. This imposes a severe overhead on the authors to achieve efficient collaboration. To address this issue, we use semantic web technologies and a discourse theory called Rhetorical Structure Theory (RST) with the aim to reduce the overhead of consistency checking. We develop OntoReST, an ontology based on RST that helps detect incoherent texts automatically. OntoReST also provides authors with valuable information about the semantic structure of texts which contributes towards enhancing documents content quality